Analisis Sinergis Institusional dalam Penyidikan dan Penuntutan Perkara Koneksitas Sebagai Upaya Menjamin Kepastian Hukum - Mulia Putri Mokodompis (Jurnal Hukum Caraka Justitia, 2026)
This research aims to analyze institutional synergies in the investigation and prosecution of connectivity cases and identify obstacles and strategies to strengthen coordination between law enforcement agencies to ensure legal certainty. The method used is normative juridical research with statutory, conceptual, and case study approaches. Data were collected through a document review of laws and regulations, as well as related literature, and observation and discussion of the practice of handling connectivity cases. Data analysis was carried out descriptively and qualitatively to describe the phenomenon of synergy and existing obstacles. The results showed that, despite the existence of a permanent investigation team mechanism and coordination efforts between institutions, synergy in the investigation and prosecution of connectivity cases was still hindered by sectoral egos, procedural differences, and inadequate regulations. Structured and sustainable synergy is needed to avoid overlapping authority, accelerate the legal process, and provide legal certainty for all parties. The implications of this research emphasize the importance of improving regulations, increasing the capacity of human resources, and developing coordination mechanisms and integrated information systems as strategic steps to strengthen institutional synergies in handling connectivity cases in Indonesia.